Penerapan Metode Pembelajaran Mnemonik Teknik Bernyanyi untuk Meningkatkan Daya Ingat Peserta Didik pada Pelajaran Matematika di Kelas III Sekolah Dasar - Anjani Pratiwi; Irma Suryani; Silvina Noviyanti (Journal on Education, 2024)
This study aims to determine the results of the application of the singing technique mnemonic method in improving memory in learning mathematics in grade III elementary school. This research was conducted at SD 80/I Muara Bulian in class IIIA students with a focus on learning mathematics. The type of research method used in this research is classroom action research (CAR) and uses the Kemmis and Mc Taggart models which include 4 stages including planning, implementation, observation, and reflection. The implementation of this study uses the Mnemonic method of singing techniques which in implementation use songs. This research approach is descriptive qualitative in the form of observations at each meeting and quantitative obtained through test results in each cycle. The results showed that the application of the singing technique mnemonic learning method could improve students' memory in learning mathematics by 59% from the initial condition which only reached 23%. Then the end of cycle I obtained a success of 41% and at the end of cycle II it increased to 82%. In addition, by applying this method in class students became enthusiastic and motivated in learning.